Aspectos Metodológicos e funcionais do atendimento educacional especializado para surdos em uma escola inclusiva - Drigo, Suely André de Araújo (2023)
This work deals with the context of provision of Specialized Educational Assistance – AEE Methodological and Functional Aspects of Specialized Educational Assistance for the Deaf in an Inclusive School. From this perspective, we assume the general objective of investigating how SEA is offered to the deaf in public schools in Uberlândia-MG. Specifically, we propose to: describe the physical structure and functioning of the AEE for the deaf in this school: pedagogical tools in the multifunctional resource rooms (MRR), assistive technologies, didactic-pedagogical resources and methodologies that consider the linguistic specificities of deaf students; analyze the School's internal and external legal documents regarding the way in which public policies for the inclusion of the deaf are established in the researched school; and to describe the functioning of the SEA offer for the deaf based on the application of a questionnaire to education professionals who work in the MRR. This research is justified by the stimulus to reflections and actions on knowledge and practices regarding the provision of SEA services for the deaf, its structure and functioning. To achieve our objectives, we elaborated the following question: What is the structure and functioning of the SEA offer for the deaf in public basic schools? The methodology adopted was based on the basic qualitative paradigm, on descriptive research as a methodological procedure, as well as on documentary research and case study. A survey of the literature on the researched area is part of the methodological theoretical framework, such as: bibliographic research (articles, chapters, books, theses and dissertations), a survey of the state of the art in theses and dissertations in the Capes database, as well as Public policies and legislation related to the education of deaf students enrolled in inclusive public schools, such as: Lei 10.436/2002, Decreto 5.626/2005, Decreto 7.611/2011, Lei 13.146/2015, and Lei 13.409/2016. The data obtained was analyzed in the light of studies pointed out by theorists such as: Ferreira (2010), Karnopp (2004), Lacerda (2006), Lopes (2017), Quadros and Karnopp (2004), Strobel (2008), Cruz (2016), which outlined the concepts of the structure and functioning of the AEE for the deaf. The data showed that the Public Policies for the inclusion of the deaf are established in the school, complying with what Decree 7.611/2011 determines, in terms of physical structure and human resources, as well as curricular accessibility. Within the scope of inclusive education for the deaf, we realize that much still needs to be conquered, learned, and implemented so that the deaf can enjoy Sign Language in different social contexts.